2006
DOI: 10.1186/1472-6947-6-7
|View full text |Cite
|
Sign up to set email alerts
|

A MEDLINE categorization algorithm

Abstract: Background: Categorization is designed to enhance resource description by organizing content description so as to enable the reader to grasp quickly and easily what are the main topics discussed in it. The objective of this work is to propose a categorization algorithm to classify a set of scientific articles indexed with the MeSH thesaurus, and in particular those of the MEDLINE bibliographic database. In a large bibliographic database such as MEDLINE, finding materials of particular interest to a specialty g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The first was to describe by one word (eg, "metabolism", "cancer" or "workrelated musculoskeletal disorders") the main subject (10).…”
Section: Methodsmentioning
confidence: 99%
“…The first was to describe by one word (eg, "metabolism", "cancer" or "workrelated musculoskeletal disorders") the main subject (10).…”
Section: Methodsmentioning
confidence: 99%
“…143 At a broader level, various studies have looked at methods for improving information retrieval from the large bibliographic databases such as MEDLINE. [144][145][146][147][148][149][150][151] Citation ranking has been compared to peer evaluation, 152 whereas methods for ranking research productivity have also been described. 153 The potential use of alternative measures of journal utility have been suggested, including Internet-based journal sessions and article download counts.…”
mentioning
confidence: 99%
“…‘The ability to search medline with the same look and feel as the rest of the Web has a lot of appeal.’ 12 The MeSH vocabulary is revised and updated annually by the NLM, and the most specific descriptors are used by indexers to represent the key concepts and terminologies found in the literature 13 . Darmoni et al 14 . found that medline 's MeSH indexing was not sufficient for sourcing highly specific material.…”
Section: Resultsmentioning
confidence: 99%